Inhibitory effect of phenothiazine- and phenoxazine-derived chloroacetamides on leishmania major growth and trypanosoma brucei trypanothione reductase - Marcu, Ana; Schurigt, Uta; Müller, Klaus; Moll, Heidrun; Krauth-Siegel, Renate; Prinz, Helge (European journal of medicinal chemistry, 2016)
A number of phenothiazine-, phenoxazine- and related tricyclics-derived chloroacetamides were synthesized and evaluated in vitro for antiprotozoal activities against Leishmania major (L. major) promastigotes. Several analogs were remarkably potent inhibitors, with antileishmanial activities being comparable or superior to those of the reference antiprotozoal drugs. Furthermore, we explored the structure-activity relationships of N-10 haloacetamides that influence the potency of such analogs toward inhibition of L. major promastigote growth in vitro. With respect to the mechanism of action, selected compounds were evaluated for time-dependent inactivation of Trypanosoma brucei trypanothione reductase. Our results are indicative of a covalent interaction which could account for potent antiprotozoal activities.
Available online 23 November 2015
Gesehen am 07.05.2020